Fulfillment of Family Needs Toward Family Satisfaction During Care in the Intensive Care Unit - Salsabila Sakanti, Aulia; Sekar Siwi, Adiratna; Susanti, Indah (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The family of patients treated in the intensive care unit often experiences anxiety and uncertainty, making it important to pay attention not only to the patients but also to their families. Meeting the needs of the patient's family is an important factor in increasing their satisfaction with health services. This study aims to analyze the relationship between the fulfillment of family needs and family satisfaction during treatment in the intensive care unit. Method: This research used a quantitative method with a cross-sectional design. The population in this study was family members of patients treated in the intensive care unit at RSUD Prof. Dr. Margono Soekarjo. A total of 83 participants were selected using accidental sampling. The research instruments used were a questionnaire to assess the fulfillment of family needs and a questionnaire to measure family satisfaction. Data were analyzed using the Spearman correlation test, and the results were presented in the form of frequency distributions and percentage tables. Result: The results showed that most respondents, amounting to 92.8%, felt that their needs were fulfilled, and 88.0% were satisfied with the services provided in the intensive care unit. Statistical tests showed a positive and significant relationship between the fulfillment of family needs and family satisfaction, with a significance value of 0.008. Conclusion: The better the fulfillment of family needs during treatment in the intensive care unit, the higher the level of family satisfaction. Hospitals are expected to continuously improve service quality by enhancing communication, emotional support, and involving families in patient care.